The Category Shifts and Translation Equivalents Found at Museum Gedong Arca Brochure: A Translation Study - Pramesti, Putu Nadia; Dewi, Putu Chrisma; Wardhana, I Gede Neil Prajamukti (JAKADARA: JURNAL EKONOMIKA, BISNIS, DAN HUMANIORA, 2025)
Translation of tourism texts is essential to bridge intercultural communication and ensure accurate transfer of cultural values to international audiences. This study investigated category shifts and equivalence strategies in the English translation of the Museum Gedong Arca brochure, a bilingual tourism text published by the Cultural Heritage Preservation Center of Bali. A descriptive qualitative method was applied through document analysis, with note-taking and documentation techniques used to collect data. The analysis was based on Catford’s (1965) framework of category shifts and Nida’s (1964, 1969) framework of translation equivalence. Results revealed 14 category shifts and 11 equivalence cases, with structure and unit shifts being most frequent, and formal equivalence slightly dominating. These findings highlight the importance of grammatical adaptation while maintaining fidelity, offering insights for improving translations of cultural heritage materials.